Uji Validasi Pengembangan Lembar Kerja Siswa Berbasis Pendekatan Saintifik - Widyasti, Ni Made Sih; IGL, Wiratma,; IW, Muderawan, (Universitas Pendidikan Ganesha, 2020)
This study aimed to: (1) develop and describe the characteristics; (2) describe and explain the validity; (3) describe and explain the practicability of Student Worksheet (LKS) based on scientific approach for chemistry learning on the chemical equilibrium topic. The type of this research was research and development with the steps carried out included: (1) data collection; (2) design of product; (3) validation of design; (4) revisions of design; (5) limited tryout; and (6) revisions of product. The developed LKS consists of five sub-topics. Content validation on LKS was done by involving two experts and two practitioners. Language validation on LKS is done by involving one linguist. A limited tryout involved 9 students of grade XI SMAN 1 Kuta Selatan. Characteristic of LKS based on scientific approach for chemistry learning on the chemical equilibrium topic, namely: (1) LKS consists of 5M learning steps with added hypothesis formulation; (2) in each LKS presented a contextual phenomenon; and (3) the language used in the LKS developed in accordance with the EYD. Validation results indicate that: (1) LKS validation results by experts and practitioners have met the valid category; (2) LKS validation results by linguists have met the linguistic rules and meet very valid categories. Based on the results of a limited tryout obtained positive response of students to learning with LKS on the implementation with very high category.